A general notion of independence of sequences of integers - John R. Burke (International Journal of Mathematics and Mathematical Sciences)
In this paper a notion of statistical independence of sequences of integers is developed. The results are generalizations of known results on independent sequences modm in the integers and more generally, independent sequences on compact sets. All that is assumed is that one has a countable partition of the integers indexed by an ordered set.